2015
DOI: 10.1016/j.rbmo.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sperm DNA fragmentation on live birth rate after IVF or ICSI: a systematic review and meta-analysis

Abstract: A systematic review and meta-analysis was conducted to evaluate the relationship between the extent of sperm DNA damage and live birth rate (LBR) per couple and the influence of the method of fertilization on treatment outcome. Searches were conducted on MEDLINE, EMBASE and Cochrane Library. Six studies were eligible for inclusion in the meta-analysis. Overall, LBR increased signficantly in couples with low sperm DNA fragmentation compared with those with high sperm DNA fragmentation (RR 1.17, 95% CI 1.07 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
241
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(258 citation statements)
references
References 51 publications
9
241
3
5
Order By: Relevance
“…Several studies have shown that the prevalence of males with high levels of SDF is greater in the infertile than in the fertile population (Spano et al, 2000;Zini et al, 2002), and that many couples with unexplained infertility have higher levels of SDF (Host et al, 1999;Oleszczuk et al, 2013). However, studies examining the effect of high SDF on assisted conception fertilization, embryo development, pregnancy, miscarriage, and birth outcomes report conflicting results; some studies report a correlation between SDF and outcomes for both in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) cycles (Collins et al, 2008;Robinson et al, 2012), others that IVF but not ICSI outcomes are influenced (Bungum et al, 2007;Zini, 2011;Osman et al, 2015), and others have found no clear association with either assisted fertilization method (Esbert et al, 2011;Ni et al, 2014). These inconsistencies may in part be attributed to study design and the use of different assays, with a recent study reporting that Comet and TUNEL assays were more predictive of clinical outcomes than SCSA (Simon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the prevalence of males with high levels of SDF is greater in the infertile than in the fertile population (Spano et al, 2000;Zini et al, 2002), and that many couples with unexplained infertility have higher levels of SDF (Host et al, 1999;Oleszczuk et al, 2013). However, studies examining the effect of high SDF on assisted conception fertilization, embryo development, pregnancy, miscarriage, and birth outcomes report conflicting results; some studies report a correlation between SDF and outcomes for both in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) cycles (Collins et al, 2008;Robinson et al, 2012), others that IVF but not ICSI outcomes are influenced (Bungum et al, 2007;Zini, 2011;Osman et al, 2015), and others have found no clear association with either assisted fertilization method (Esbert et al, 2011;Ni et al, 2014). These inconsistencies may in part be attributed to study design and the use of different assays, with a recent study reporting that Comet and TUNEL assays were more predictive of clinical outcomes than SCSA (Simon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although the data collected in this study were derived from men of unproven fertility, our results are relevant when considering assisted reproduction techniques for infertile men, where higher levels of sperm DNA fragmentation may be associated with increased chances of early pregnancy failure after IVF and ICSI (Zini et al, 2008;Robinson et al, 2012;Zhao et al, 2014;Osman et al, 2015). Earlier studies have shown that, compared with spermatozoa recovered after a general washing step, sperm from the same semen sample binding to hyaluronic acid were more mature in relation to cytoplasmic and nuclear condensation (Huszar et al, 2003;Yagci et al, 2010) and that hyaluronic-acid-selected sperm from crude semen samples had low levels of DNA fragmentation (Yagci et al, 2010).…”
Section: Changes In Sperm Hyaluronic-acid-binding and Hyperactive Motmentioning
confidence: 99%
“…Попытки метаанализа данных о значении измерения ФДС в репродукции показывают, что од-нозначного ответа дать нельзя, результаты весьма про-тиворечивы: нет данных о предиктивности теста, не подтверждаются данные о преимуществе ИКСИ перед ЭКО при повышенной фрагментации ДНК [84,[93][94][95][96]. Авторы отмечают низкое качество рандомизированных исследований и считают, что рекомендовать тест для универсального использования рано: есть работы, в ко-торых не найдено различий исхода ВРТ и беременно-сти при различиях в содержании ФДС, исследованы небольшие гетерогенные популяции, исследования про-водятся разными методами и различаются по дизайну экспериментов.…”
Section: корреляционная электронная микроскопияunclassified